2007
DOI: 10.1016/j.cemconres.2006.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Effects and interactions of temperature and stress-level related damage on permeability of concrete

Abstract: International audienceThe objective of this study is to investigate damage-temperature-stress level-permeability interactions in structural concrete. The tests are performed on hollow cylindrical concrete specimens, subjected to compressive loading and temperature up to 150 °C. The results emphasize that at stress levels lower than 80% of the peak stress, the variation of permeability is small and it is slightly influenced by the stress. As a matter of fact, the permeability under load is smaller than the perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
117
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 223 publications
(130 citation statements)
references
References 16 publications
9
117
0
4
Order By: Relevance
“…It has been reported that compressive and tensile loads can affect the water permeability, gas permeability and chloride penetration (Banthia et al 2005;Choinska et al 2007;Lim et al 2000;Sugiyama et al 1996;. By summarizing the results of these studies, two main conclusions can be drawn.…”
Section: Derivation Of Loading Effect Factor F(εd)mentioning
confidence: 71%
“…It has been reported that compressive and tensile loads can affect the water permeability, gas permeability and chloride penetration (Banthia et al 2005;Choinska et al 2007;Lim et al 2000;Sugiyama et al 1996;. By summarizing the results of these studies, two main conclusions can be drawn.…”
Section: Derivation Of Loading Effect Factor F(εd)mentioning
confidence: 71%
“…For example, mechanical properties of cracked concrete were studied in [16]- [21], water transport properties in [22]- [27], chloride transport in [28]- [34]. In addition, just one or two important parameters were determined in the majority of experimental investigations of the particular concrete mixes, which made the applicability of obtained results to other cases rather limited.…”
Section: Introductionmentioning
confidence: 99%
“…Effects of temperature and damage on permeability of concrete was experimentally studied e.g. in [3] or [4]. Numerical model of the influence of damage, which is expressed by the damage parameter, on the permeability of concrete was studied in [5].…”
Section: Introductionmentioning
confidence: 99%